2020
DOI: 10.1002/jlb.1ma0420-635r
|View full text |Cite
|
Sign up to set email alerts
|

Generation of cell-derived matrices that support human NK cell migration and differentiation

Abstract: Human NK cells are effectors of the innate immune system that originate from hematopoietic precursors in the bone marrow. While stromal cell lines that support NK cell development from hematopoietic precursors are often used to generate mature NK cells from lymphoid precursors in vitro, the nature of contributing factors of these stromal cells to the generation of functionally mature NK cells has been poorly described. Previous studies have shown that developing NK cells adhere to, and migrate on, developmenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(98 reference statements)
0
14
0
Order By: Relevance
“…CD-ECMs from stromal, endothelial and epithelial cells could improve the function of specialized cell types, such as podocytes ( Satyam et al, 2020 ), chondrocytes ( Wei et al, 2015 ; Yang et al, 2018 ; Zhang et al, 2019 ), hepatocytes ( Grant et al, 2017 ; Guo et al, 2017 ), Schwann cells ( Xiao et al, 2016 ), as well as promote natural killer cell differentiation ( Lee et al, 2020 ).…”
Section: Applications Of Cd-ecmmentioning
confidence: 99%
“…CD-ECMs from stromal, endothelial and epithelial cells could improve the function of specialized cell types, such as podocytes ( Satyam et al, 2020 ), chondrocytes ( Wei et al, 2015 ; Yang et al, 2018 ; Zhang et al, 2019 ), hepatocytes ( Grant et al, 2017 ; Guo et al, 2017 ), Schwann cells ( Xiao et al, 2016 ), as well as promote natural killer cell differentiation ( Lee et al, 2020 ).…”
Section: Applications Of Cd-ecmmentioning
confidence: 99%
“…Thus, MSC close to the tumor have some features of repairing tissue MSC [ 189 , 190 , 191 ]. Additionally, NK cells come across with several healthy cells before reaching tumor cells [ 192 , 193 , 194 ]. It is conceivable that NK cells may interact with a tumor-budding spheroid during the progressive growth of the neoplastic mass [ 195 , 196 , 197 , 198 ].…”
Section: Tumor Cell Organoids: a More Reliable 3d Model To Study Tumor Cell Biology And Tumor-nk Cells Interactions?mentioning
confidence: 99%
“…S3A). To monitor NK cell migration we cocultured primary NK cells with EL08.1D2 cells, which have previously been shown to support spontaneous NK cell migration (32,33) and produce extracellular matrix (34), and live imaged them for 24 h capturing photos every 2 minutes (Fig. 3B).…”
Section: Fap Inhibition Reduces Primary Human Nk Cell Migrationmentioning
confidence: 99%
“…2D migration studies were done as previously reported 31,32,65 . In brief, EL08.1D2 stromal cells were grown to a confluent monolayer on flat-bottomed 96 well ImageLock plates (Essen Bioscience) pre-coated with 0.1% gelatin (Stemcell Technologies).…”
Section: D Cell Migration Studiesmentioning
confidence: 99%